Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3177/jnsv.65.421
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin Supplementation Prevents Lipid Accumulation and Induces Skeletal Muscle-Fiber Hypertrophy in Rats

Abstract: Diosgenin (Dio) is a steroid sapogenin found in plants such as Dioscorea species, and is recognized as a phytochemical against various disorders as well as a natural precursor of steroidal drugs. The present study used rats fed high-cholesterol (Chol) diets supplemented with or without 0.5% Dio for 6 wk to investigate the effects of dietary Dio on lipid metabolism. Dio supplementation significantly increased serum high-density lipoprotein Chol concentrations and fecal Chol content, and significantly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…In Wistar rats fed with high-cholesterol diets, administration of 0.5% diosgenin for 6 weeks significantly increased serum HDL concentrations and fecal cholesterol contents, but decreased the levels of hepatic TC, TG and fecal bile acids. The potential lipid-lowering mechanism might be through activating the catabolic pathway of AMPK, thus inhibiting cholesterol absorption and facilitating cholesterol excretion [162]. Resistant starch is a component of starch that is not digested in the small intestine but fermented by the microbiota in colon and produces short-chain fatty acids [163].…”
Section: Dioscoreae Rhizoma (Shanyao)mentioning
confidence: 99%
“…In Wistar rats fed with high-cholesterol diets, administration of 0.5% diosgenin for 6 weeks significantly increased serum HDL concentrations and fecal cholesterol contents, but decreased the levels of hepatic TC, TG and fecal bile acids. The potential lipid-lowering mechanism might be through activating the catabolic pathway of AMPK, thus inhibiting cholesterol absorption and facilitating cholesterol excretion [162]. Resistant starch is a component of starch that is not digested in the small intestine but fermented by the microbiota in colon and produces short-chain fatty acids [163].…”
Section: Dioscoreae Rhizoma (Shanyao)mentioning
confidence: 99%
“…However, muscle contractions depend on the number and size of the fibres [ 33 ]. The analysis of the muscle fibres was calculated by measuring the CSA, and the diameter [ 27 ]. These results showed that the HFD group had a decreased diameter, and CSA in their skeletal muscles, which led to muscle fibre atrophy, when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the HFD group had a decreased diameter, and CSA in their skeletal muscles, which led to muscle fibre atrophy, when compared to the control group. Previous studies showed that the high-fat-diet-fed rats CSA, number of fibres, and diameters of their soleus and quadriceps had decreased, which led to reduced muscle weight and also impaired force of muscle contraction [ 27 , 34 , 35 ]. Conversely, the skeletal muscle parameters from the histological analysis in our study of the naringin treatment were higher than both the HFD and the HFD + SIM groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…117 The cholesterol transport system not only inhibits the intestinal absorption of cholesterol but also carries cholesterol from peripheral tissues to the liver, excreting it into bile or forming free cholesterol, which is then excreted through the intestine to the body. 118 Diosgenin can promote fecal cholesterol excretion and inhibit cholesterol absorption in mice and rats; 85,107,119 this effect is related to Niemann-Pick C1-Like 1 (NPC1L1) and ATP-binding cassette G5/8(ABCG5/8). NPC1L1 is a transmembrane protein highly expressed in the intestine and liver, which mediates the excretion of intestinal sterols and hepatic cholesterol.…”
Section: Inhibition Of Intestinal Cholesterol Absorption/promotion Of...mentioning
confidence: 99%